Aging and Inflammation - Singh, Amit; Schurman, Shepherd H; Bektas, Arsun; Kaileh, Mary; Roy, Roshni; Wilson, 3rd, David M; Sen, Ranjan; Ferrucci, Luigi (Cold Spring Harbor perspectives in medicine, 2024)
Aging can be conceptualized as the progressive disequilibrium between stochastic damage accumulation and resilience mechanisms that continuously repair that damage, which eventually cause the development of chronic disease, frailty, and death. The immune system is at the forefront of these resilience mechanisms. Indeed, aging is associated with persistent activation of the immune system, witnessed by a high circulating level of inflammatory markers and activation of immune cells in the circulation and in tissue, a condition called "inflammaging." Like aging, inflammaging is associated with increased risk of many age-related pathologies and disabilities, as well as frailty and death. Herein we discuss recent advances in the understanding of the mechanisms leading to inflammaging and the intrinsic dysregulation of the immune function that occurs with aging. We focus on the underlying mechanisms of chronic inflammation, in particular the role of NF-κB and recent studies targeting proinflammatory mediators. We further explore the dysregulation of the immune response with age and immunosenescence as an important mechanistic immune response to acute stressors. We examine the role of the gastrointestinal microbiome, age-related dysbiosis, and the integrated stress response in modulating the inflammatory "response" to damage accumulation and stress. We conclude by focusing on the seminal question of whether reducing inflammation is useful and the results of related clinical trials. In summary, we propose that inflammation may be viewed both as a clinical biomarker of the failure of resilience mechanisms and as a causal factor in the rising burden of disease and disabilities with aging. The fact that inflammation can be reduced through nonpharmacological interventions such as diet and exercise suggests that a life course approach based on education may be a successful strategy to increase the health span with few adverse consequences.